Retraction: A near-infrared laser and H2O2 activated bio-nanoreactor for enhanced photodynamic therapy of hypoxic tumors. (31st October 2022) - Deng, Liming; Sheng, Danli; Liu, Mingzhu; Yang, Lu; Ran, Haitao; Li, Pan; Cai, Xiaojun; Sun, Yang; Wang, Zhigang
Abstract : Retraction of 'A near-infrared laser and H2 O2 activated bio-nanoreactor for enhanced photodynamic therapy of hypoxic tumors' by Liming Deng et al., Biomater. Sci., 2020, 8, 858–870, ; https://doi.org/10.1039/C9BM01126A .